2013
DOI: 10.1002/jssc.201300063
|View full text |Cite
|
Sign up to set email alerts
|

In‐capillary reactant mixing for monitoring glycerol kinase kinetics by CE

Abstract: CE was used for the first time to study the two-substrate enzyme glycerol kinase. The capillary was used as a nanoreactor in which the enzyme and its two substrates glycerol and adenosine-5'-triphosphate were in-capillary mixed to realize the enzymatic assay. For kinetic parameters determination, reactants were injected (50 mbar × 5 s) as follows: (i) incubation buffer; (ii) adenosine-5'-triphosphate; (iii) enzyme, and (iv) glycerol. Enzymatic reaction was then initiated by mixing the reactants using electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, mixing more than two reactants by EMMA is difficult [8,25,26,28]. In this work, even when combining EMMA to a zero potential amplification step [8,9,26,27] the ADP produced was below the LOQ (about 0.20 M). This is certainly due to a partial reactant plug overlapping insufficient to trigger the enzymatic reaction.…”
Section: Preliminary Study Of In-capillary Mixingmentioning
confidence: 67%
See 1 more Smart Citation
“…However, mixing more than two reactants by EMMA is difficult [8,25,26,28]. In this work, even when combining EMMA to a zero potential amplification step [8,9,26,27] the ADP produced was below the LOQ (about 0.20 M). This is certainly due to a partial reactant plug overlapping insufficient to trigger the enzymatic reaction.…”
Section: Preliminary Study Of In-capillary Mixingmentioning
confidence: 67%
“…Electrophoretically mediated microanalysis (EMMA) is the most widely used in-capillary mixing technique for enzymatic studies [24][25][26][27]. However, mixing more than two reactants by EMMA is difficult [8,25,26,28].…”
Section: Preliminary Study Of In-capillary Mixingmentioning
confidence: 99%
“…In EMMA, reactants are sequentially injected onto the capillary and mixed based on their differential electrophoretic mobilities allowing for the enzymatic reaction to occur on-line (Figure 5A). [12,8388] In comparison to traditional enzyme screening assays, lower IC50 values have been determined using EMMA. Lower observed inhibition has been attributed to the decreased incubation time typical in EMMA.…”
Section: Targetsmentioning
confidence: 99%
“…[86] EMMA was also demonstrated for a two substrate enzyme, glycerol kinase, with four reactant plugs: incubation buffer, enzyme and two distinct substrate plugs, mixed in-capillary. [88] Small-scale screening of Chinese herbs and other crude products against enzymatic targets by EMMA with UV detection demonstrated the utility of CE in screening of complex test compound mixtures, where potential optical interference is reduced compared to other optical platforms. [8387] While EMMA requires very little enzyme per assay optimal conditions for the enzymatic reaction may be easier to achieve in well plate format.…”
Section: Targetsmentioning
confidence: 99%
“…4 To develop electromagnetophoretic applications more extensively to various microscale systems, it will be crucially important to investigate in detail the phenomena of the electromagnetophoretic convection of the medium. Any study of the convection of a liquid in micro-systems will have a more important meaning as a novel technique of micro-mixing, since it has been widely studied as a bottle-neck technique in μTAS, 11 lab-on-a-chip, 12,13 capillary systems, [14][15][16] and many microchannel methods. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Some reviews have also been reported concerning effective mixing in microchannels 34,35 and in small-scale production.…”
Section: Introductionmentioning
confidence: 99%